The ‘Transparency Effect’ in Pharmaceutical ESG Reports - Andrea Fenice; Renzo Mocini (Iperstoria)
As the pharmaceutical sector has become increasingly competitive, companies have adopted a plethora of strategies and practices not only to publicise their products but also to be perceived by stakeholders as transparent and, by way of implication, honest and ethical. Drawing on a corpus of English-language Environmental, Social and Governance (ESG) reports, this study investigates the complexity and dynamism of the discursive strategies used by leading pharmaceutical companies listed on the stock exchange to build and enhance an image of transparency and credibility. By distinguishing between the level of the utterance – what is being communicated – and the enunciational level (Greimas & Courtés 2007; Greimas 1983), which regards the writer and the context of enunciation, this paper conducts a semio-linguistic analysis in an attempt to explore different construals of transparency and opacity. The discourse of pharmaceutical companies is revealed as a sophisticated communicative construct, where various strategies are employed to create meaning effects that are used to foster an image of transparency and boost stakeholders’ trust.